Knowledge for results and the efficiency of public agencies in Colombia - Diego Arisi; Alix Cortés; Diego Delic; Martín Antonio Rossi (Inter-American Development Bank (IDB), 2022)
This paper documents the effects of an intervention on knowledge sharing, in which information embedded in efficient private organizations is used to improve bureaucratic procedures of public agencies. In particular, it analyzes the impact of the Knowledge for Results (K4R) program on the efficiency of public agencies in Colombia. The findings of the study indicate that K4R is associated with a statistically significant improvement in operational efficiency. The paper presents two examples of K4R. In the first example, K4R reduced the time that local ombudsman offices need to deal with incoming petitions from citizens. In the second example, K4R reduced the time that oncology patients spend in an emergency clinic until they are discharged from the hospital. These time reductions are quantitatively relevant and imply efficiency gains of between 25 and 40 percent relative to pre-program levels.
Keywords: H43; H75; 330; new public management; knowledge management; policy evaluation